Pooled Prevalence and Determinants of Completion of Maternity Continuum of Care in Sub-Saharan Africa: A Multi-Country Analysis of Recent Demographic and Health Surveys - Hunie Asratie, Melaku; Belay, Daniel Gashaneh (Frontiers in Global Women's Health, 2022)
Background: Improving the coverage of completion of maternity continuum of care is the priority area of sub-Saharan African countries to achieve the sustainable development goal. Despite this, information is scant about the pooled prevalence of completion of maternity continuum of care and its determinants in sub-Sahara Africa countries. Therefore, this study was aimed to assess the pooled prevalence of completion of maternity continuum of care and its determinants among women in sub-Saharan African countries. Methods: The study was conducted based on Demographic and Health Survey data from 33 sub-Saharan African countries from 2010 to 2020. The total sample size of 337297 post-partum period women with children aged 0-36 months was employed in the analysis by STATA version 14. A multilevel logistic regression model was fitted, and ICC, MOR, PCV, and deviance were used for model fitness and comparison. Adjusted odds ratio with its 95% confidence interval was presented. Variables with a P-value of <0.05 were declared significant determinants of completion of the maternity continuum of care. Results: The pooled prevalence of completion of maternity continuum of care was 35.81%; 95% [35.64%, 35.9%]. Educational attainment higher (Adjusted Odds Ratio [AOR=3.62; 95% CI (Confidence Interval) 2.25, 4.46], wanted pregnancy [AOR=2.51; 95% CI 1.82, 3.12], history of terminated pregnancy [AOR=3.21; 95% CI 2.86, 4.21], distance was not a big problem [AOR=2.11; 95% CI 1.68, 2.36], women primary decision maker [AOR=2.15; 95% CI 2.02, 2.87], not use traditional medication during pregnancy [AOR=1.01; 95% CI 1.00, 1.45], antenatal care visit within second trimester [AOR=2.76; 95% CI 2.01, 3.47], told about pregnancy complication [AOR=2.73; 95% CI 2.10, 3.21], health care provider support [AOR=1.77; 95% CI 1.02, 2.44], and being eastern and western Africa [AOR=1.55; 95% CI 1.11, 2.44, and AOR=2.01; 95% CI 1.88, 2.76 respectively] were determinant factors of completion of maternity continuum of care. Conclusions: Completion of maternity continuum of care in sub-Sahara African countries was low. Emphasis on women's education, type, and history of pregnancy, distance to the nearby health facility, region, assessing the exposure to traditional medication, and telling complications of pregnancy with health care provider support can improve the outcome variable.